Devotion to Roudhoh Kindergarten Plus Teachers Using the Learning Apps Application - Idat Muqodas; Luthfiyyah Ghaida Sajidah; Nafa Hidayaturrachman; Nida Imtinan jayaputri; Ria Yuliana Prasojo (Experimental Student Experiences, 2024)
This article reviews technology-based learning for early childhood. This study aims to provide learning knowledge to teachers on how to create technology-based learning media, especially e-learning on the web, namely learning apps. This type of research is qualitative research while the research instrument is the observation of the researcher finding the result that the teacher can make learning media through learning apps with various themes. Current technological developments make it easier for humans to carry out various activities. Learning using learning apps can add experience and insight for teachers. As well as making it easier for teachers to give assignments to children that can be used anywhere and anytime, children can reuse them when they want to learn while playing.